Genetic potential and heritability estimates of yield and yield associated traits in rape seed Brassica napus L - Shaukat, Sadia; Raziuddin, Dr; Khan, Fahim Ullah; Khalil, Ibni Amin (International Journal of Environment, 2015)
To investigate genetic variability and heritability, eight Brassica napus genotypes were evaluated at New Developmental Research Farm, Faculty of Agriculture. Peshawar University, during 2010-11. Analysis of variance revealed significant differences (P≤0.01) among Brassica napus genotypes for all the studied characters. Mean values showed that maximum primary branches plant-1 (15) was observed for genotype PGRI-8, plant height (220.66 cm) for genotype CH-6 and PGRI-8, pods main raceme-1 (96.33) for genotype CH-1, pods plant-1 (994) for genotype PGRI- 8, pod length (8.3 cm) for genotype PGRI- 7, seeds pod-1 (27) for genotype CH-1, 1000-seed weight (3.97 g) for genotype CH-2, and seed yield plant-1 (91.1 g) for genotype PGRI-8. In t terms of heritability values, high broad sense heritability estimates were observed for primary branches plant-1 (0.83), plant height (0.78), pods main raceme-1 (0.65), seeds pod-1 (0.61), 1000-seed weight (0.61), while moderate heritability values were recorded for pod length (0.57), pods plant-1 (0.55), and seed yield plant-1 (0.50). In conclusion, the significant differences among Brassica napus genotypes showed that there is sufficient variability for effective selection. The trend of heritability (moderate to high) in the present study indicates that there is more genetic control and selection should lead to quick improvement. Furthermore genotype PGRI-8 surpassed all other genotypes in yield and yield component and could be used in future breeding programs. DOI: http://dx.doi.org/10.3126/ije.v4i2.12661 International Journal of Environment Vol.4(2) 2015: 330-340